TAQLID ITTIBA FOR MUKALLAF IN THE IMPLEMENTATION OF ISLAMIC LAW ON POSITIVE LAW IN INDONESIA - Kusmayanti, Hazar (Universitas Islam Negeri Raden Fatah Palembang, 2020)
The Indonesian people in fact use their minds not on the basis of the Qur'an and the Sunnah is only limited to taqlid ittiba the religious scholars who are not necessarily truthful can be justified. The purpose to understanding of taqlid ittiba and to obtain the consequences of taqlid ittiba for Muslim in implementing Islamic Law and Positive Law. Research methods by using normative research methods or library law research in finding taqlid ittiba material for mukallaf. The results showed that the implementation of taqlid ittiba for mukallaf performed by Muslims is still a lot that is not in accordance with the teachings of Allah SWT and does not follow the Sunnah of Rasullah SAW. The implementation of taqlid ittiba that is wrong can harm oneself and others who can be troubling to the surrounding community. Someone who carries out taqlid ittiba that is not appropriate in the Qur'an and Sunnah has a legal consequence that is sinful because it does not follow the commands of Allah SWT and Rasul while according to the Law Positive in Indonesia taqlid ittiba allowed for someone who is an adult and does not violate the existing Positive Law so as to create peace between religious communities.